THE RHEOLOGICAL PROPERTIES OF BLOOD IN THE MOST ACUTE STAGE OF ISCHEMIC STROKE AND THEIR RELATION TO THE SEVERITY OF NEUROLOGICAL IMPAIRMENT - M. N. Azhermacheva; D. M. Plotnikov; O. I. Aliev; V. M. Alifirova; M. B. Plotnikov; K. I. Burkova (Бюллетень сибирской медицины, 2013)
The study evaluated the rheological parameters of blood: blood viscosity, plasma viscosity, hematocrit, red blood cell aggregation and deformability. The severity of the patients was assessed by clinical scales:Glasgowcoma scale, the scale NIHSS, Barthel index. The study found that in the acute phase of ischemic stroke increased blood viscosity by increasing red blood cell aggregation and reduced erythrocyte deformability. The increase in the viscosity of the blood in acute ischemic stroke is accompanied by increased severity of neurological disorders.